Numerical Simulation Study of Pore-Throat Evolution of Upper Paleozoic in Ordos Basin, China - Qing Cao; Zhangxing Chen; JingZhou Zhao; Jiacheng Dang; Jiaxuan Song; Bin Chen (Geofluids)
The parameters of grain size, contents of silica, kaolinite, hydromica, calcite, and a geological time of tight sandstone reservoirs in Upper Paleozoic in Ordos basin were researched thoroughly, and the impact of the diagenetic evolution process of different sandstone types on porosity and throats was analyzed, based on the quantitative statistics from thin sections, measurements of porosity and permeability, and conventional and constant-rate mercury injection tests. We not only build the evolution of porosity through process-oriented numerical simulations during the geological time but also establish effect-oriented numerical simulations between porosity and different diagenesis parameters. Furthermore, we set up a fitting relationship between diagenetic factors and pore throats in different gas-bearing reservoirs. Differentiation results in the evolution of porosity and a pore-throat system of sandstone types have clear characteristics, such as lithic quartz sandstones of the He 8 Member in the Sulige area and quartz sandstones of the Shan 2 Member in the Yulin area. The fitting results show that the main factors influencing the evolution of porosity and a pore-throat system are grain size and siliceous cement, which can also be validated by the measured data on two gas-bearing intervals. The results are important to a deep understanding of the relationship between the reservoir continuing to experience porosity and permeability evolution and the timing of petroleum charging into the reservoir and can also be applied elsewhere as a quick means in high grading areas of risks during field development.